AN ANALYSIS OF TRANSITIVITY IN JAVA LIBRARY - Raphaël Muloway MUAMBILA BANTU (Ziglôbitha)
Abstract : This article is an investigation into the language of Java Library with a view to find out if and how the ideational function of language is instantiated in it. It is a transitivity analysis of some constructs of Java Library in order to discover if and how Java developers construe the experience in this rubric of Java, an object-oriented programming language. The data of this research were collected from some reference books of this programming. The analysis reveals that Java developers resort to transitivity in order to construe the experience in Java Library. Another finding is that material processes are more used than relational processes in order to construe meaning in Java Library. With regard to material processes, the findings reveal that the configuration Process + Goal is more used than the configuration Process only. Besides, the configuration Actor + Process and Actor + Process + Goal are not used in the construal of meaning in Java Library. As regards, relational processes, the study reveals that intensive attributive processes are more used than possessive identifying, circumstantial identifying and intensive identifying processes. Moreover, possessive identifying and circumstantial attributive processes are not used in the construing of meaning in Java library. Last, Java developers do not resort to mental processes to express content in Java Library. Keywords: Transitivity, Java, Java Library